Environmental risk management based on city air data monitoring - Vtorushina, Anna Nikolaevna (Вестник Томского государственного университета. Химия)
This study aims to investigate the quality of air in a city located in Sibe-ria. A comparison was made between potential sources of harmful effects on air quality and air pollution in different parts of the city. It was found that traffic and thermal power plants are the main causes of air pollution. An environmental risk assessment was con-ducted based on data about air pollution levels. Cumulative hazard index showed a sig-nificant impact on respiratory health, increasing the risk of adverse health effects. The proposed measures to reduce environmental risks were based on an analysis of sources of negative impacts and substances emitting to the atmosphere. In summary, it can be argued that environmental quality monitoring is an essential component of environmental risk management. Information about pollution levels al-lows to assess the level of risk in a particular area and predict potential consequences for human health. These data also serve as a basis for developing measures to minimize environmental risks.